Knowledge and attitude of mothers on operative medical acceptance of women as a contraceptive option in the work area of Sindar Raya Puskesmas, Semalungun district - Arsiaty Sumule; Andre Bastian Mani (Institute of Computer Science (IOCS), 2022)
Family planning has become one of the pillars of the mother-loving movement, so that it can be achieved by limiting the number of children, not too old or too young to get pregnant, not too short pregnancy intervals, increasing mental and physical health so that pregnant women are at an optimal level of well-being. Tubectomy is the most effective, inexpensive, safe method of family planning, and has high demographic value. The tubectomy contact method is a minor operation and is a permanent contraceptive which is carried out by acting on both fallopian tubes so that it blocks the meeting of the egg (ovum) with sperm cells (sperm). The purpose of this study was to determine the knowledge and attitudes of mothers towards women's operative medical acceptance as a contraceptive option in the Working Area of the Sindar Raya Health Center, Simalungun Regency in 2017. The research design used was descriptive with a sample of 58 people using total sampling. This research was conducted in May-July 2017. The research instrument used a questionnaire which was first tested with a content validity test. From the results of the study it was found that 22 people (37.9%) had good knowledge, 29 people (50.0%) had sufficient knowledge and 7 people (12.1%) had less knowledge. The majority of respondents who had a negative attitude were 35 people (60.3%) and respondents who had a positive attitude were 23 people (39.7%). It is expected that mothers will seek as much information about tubectomy contraception methods from electronic media, mass media, and health workers. Thus, so that mothers understand more about the method of tubectomy contraception in particular.